(untitled) (Forum Penelitian Agro Ekonomi, 2016)
English The performance of soybean production, productivity, and area of production as well as the demand, for this commodity are intensely discussed in this article. On the other hand, the opportunity to increase the domestic production can be led by enhancing the utilization of the new sources of production growth such as: (1) Expansion of production area through extensification program and increased cropping index, (2) Increasing productivity (tort/ha), (3) Increasing yield stability per unit of area. (4) Reducing the yield gap between recommended technology and yield at farm level, and (5) Reducing yield loss during harvest and post harvest handling. In addition, the discussion also involves other aspects such as: financial feasibility of soybean farming and its competitiveness to other competing crops, comparative advantage of effort to blow up domestic production compared with import, and economic incentive of government policy to the soybean farming in three provinces, namely: West lava. Central Java. and Lampung. ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â Indonesian Dalam makalah ini dikemukakan perkembangan produksi, produktivitas, dan kebutuhan serta perkembangan ekspor dan impor kedelai di Indonesia. Sedangkan tambahan produksi kedelai yang mampu dihasilkan dapat ditempuh dengan pemanfaatan sumber pertumbuhan produksi kedelai: (1) Perluasan areal tanam (ekstensifikasi dan peningkatan indeks pertanaman), (2) Peningkatan produktivitas (hasil/ha), (3) Peningkatan stabilitas hasil per satuan luas, (4) Mempersempit senjang hasil antara teknologi rekomendasi dengan hasil di tingkat petani, dan (5) Menekan kehilangan hasil panen dan pasca panen. Lebih lanjut, pada makalah ini juga dibahas tentang kelayakan finansial dan keuntungan kompetitif usahatani kedelai dibandingkan dengan komoditas kompetitornya, keunggulan komparatif upaya memacu produksi kedelai di dalam negeri dibandingkan dengan impor, serta insentif ekonomi kebijaksanaan pemerintah pada usahatani kedelai di tiga wilayah penelitian pengembangan produksi kedelai yaitu; Jabar, Jateng, dan Lampung.